2015
DOI: 10.1002/2015jb012163
|View full text |Cite
|
Sign up to set email alerts
|

Variability in magnitude of paleoearthquakes revealed by trenching and historical records, along the Haiyuan Fault, China

Abstract: Paleoseismology provides fundamental data for generalizing earthquake recurrence behavior, by revealing past surface‐rupturing events. Determining the size of paleoseismic events is notoriously more challenging than their timing. Paleoearthquakes exposed in trenches are vaguely defined as large enough to break to the surface and often assumed to be similar in size. Here we show an example where the paleoseismic record includes events of both moderate and large magnitudes. At the Salt Lake site on the active le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 69 publications
1
35
0
Order By: Relevance
“…Zhang et al (2005) and Ren et al (2015) found that the Haiyuan fault may rupture in segments. Liu-Zeng et al (2015) identified three or four seismic events on the Haiyuan fault since A.D. 1500 based on trench and historical records. In addition, Chen et al (2018) systematically measured offset landforms along the Laohushan fault using lidar data.…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al (2005) and Ren et al (2015) found that the Haiyuan fault may rupture in segments. Liu-Zeng et al (2015) identified three or four seismic events on the Haiyuan fault since A.D. 1500 based on trench and historical records. In addition, Chen et al (2018) systematically measured offset landforms along the Laohushan fault using lidar data.…”
Section: Geological Settingmentioning
confidence: 99%
“…Studying paleoseismology of the fault can provide important information to understand strain release process and recurrence behavior of the fault and possibility of next large earthquake (Akciz et al, ; Berryman et al, ; Scharer et al, ; Shimazaki & Nakata, ). The paleoseismic history and rupture pattern of the Laohushan and Haiyuan faults have been studied in detail (Y. Li et al, ; B. C. Liu et al, ; Liu‐Zeng et al, , ; Ran et al, ; P. Z. Zhang, Molnar, Zhang, et al, ; ). In contrast, the LLLF is located in a high‐altitude and remote area, with difficult access, and thus, relatively few studies have focused on the LLLF.…”
Section: Introductionmentioning
confidence: 99%
“…Channels have steep longitudinal profiles, transporting coarse sediment from mountain to piedmont, building boulder alluvial fans or cutting deep canyons. In this steep environment, few geomorphic settings in the study area are optimal for paleoseismology, like pull‐apart basins (e.g., Daëron et al, ; Liu‐Zeng et al, ; Rockwell et al, ; Scharer et al, ), shutter ridges, or other large morphological depressions (e.g., Fumal et al, ; Lienkaemper & Williams, ; Sieh, ) or distal fans (e.g., Grant & Sieh, ; Klinger et al, ) of fine‐grain deposits. Nonetheless, we found a pair of sites with local ponding of sediments caused by oblique slip along the fault.…”
Section: Seismotectonic Settingmentioning
confidence: 99%
“…In addition, paleoseismological trenches along the Haiyuan fault suggest that six events of different magnitude ruptured the central Haiyuan strand in the last 3,500–3,900 years (Liu‐Zeng et al, ). Historical medium‐size earthquakes have also been documented along the 1920 rupture section (LiuZeng et al, ).…”
Section: Introductionmentioning
confidence: 99%